Concentration of PM10 in the Metropolitan Area of Costa Rica, Central America: chemical composition and potential sources - Herrera-Murillo, Jorge (2010)
Measurements of metals and inorganic ions were carried out on PM10. Sampling was made in five sites distributed in San José, Heredia and Belén cities. Samples were collected using Thermo Andersen PM10 high volume samplers with glass fiber and quartz filters. The ions SO4 2- , NO3- , Cl- , F- , PO43- , NH4 + , K+ , Na+ , Ca2+, Mg2+ were analyzed by ion chromatography and in the case of metals V, Cu, Cr, Pb, Ni, Mn, Fe, Al using an atomic absorption spectrometer with a graphite furnace attachment. The results indicated that SO42- was the most abundant ion, and with respect to metals, Al and Fe had the highest concentration. Spearman correlation, applied to all data, showed a high correlation between SO42- , NO3- and NH4+ indicating a common anthropogenic origin. From the metal species that were assessed only Pb and Cu presented enrichment factors higher than 10, indicating an anthropogenic contribution. Particles collected in the industrial zone of Belén showed the highest level of acidity and metal content.